I.v.22 Minutes, - Labour Party (Ireland) (2009)
Minutes and supporting documentation of one meeting of the Management Committee which took place 15 Dec 2009. Includes supporting documentation for meeting, dated 14 Jan 2009. Also includes: correspondence to the General Secretary from Sean Quinn, Quinn Group, Derrylin, County Fermanagh concerning the Party Spokesperson on Finance comments regarding Quinn Groups relationship with Anglo-Irish Bank, dated 22 Jan 2009; and ‘New Members Survey’ 2009. (27 pp) These materials are currently not available for consultation but this will be reviewed in 2027.